THE IMPACT OF BRAND IMAGE, ADVERTISING, QUALITY OF SERVICE ON REPURCHASE INTENTION, AND ELECTRONIC WORD OF MOUTH MEDIATED BY CUSTOMER EXPERIENCE AT SHOPEE ONLINE STORE - Michael, Michael; Kristiyono, Yokie Radnan (Universitas Trisakti, 2022)
There is the goal of this study, namely to determine the effect of Brand Image on Consumer Experience, Advertising on Consumer Experience, Service Quality on Consumer Experience, Consumer Experience on Repurchase Intention, Consumer Experience on Electronic Word of Mouth, as well as knowing the effect of Consumer Experience that mediates Brand Image on Repurchase Intention, Consumer Experience mediating Advertising on Repurchase Intention, Consumer Experience mediating Service Quality on Repurchase Intention, Consumer Experience mediating Brand Image on Electronic Word of Mouth, Consumer Experience mediating Advertising on Electronic Word of Mouth, and Consumer Experience which mediates Service Quality in Electronic Word of MouthThe sample collection technique used in this study was non-probability sampling – purposive sampling. The results of testing the hypothesis indicate that all hypotheses are supported, namely: Brand Image has a positive influence on the Shopee online store Consumer Experience, Advertising has a positive influence on the Shopee online store Consumer Experience, Service Quality has a positive influence on the Shopee online store Consumer Experience, Consumer Experience has positive impact on Shopee online store Consumer Repurchase Intention, Consumer Experience has a positive effect on Shopee online store Consumer Electronic Word of Mouth, Consumer Experience positively mediates Brand Image on Shopee online store consumer Repurchase Intention, Consumer Experience positively mediates Advertising on Intention Shopee online shop Consumer Repurchase, Consumer Experience positively mediates Service Quality on Shopee online shop Consumer Repurchase Intention, Consumer Experience mediates positively Brand Image Electronic Word of Mouth Shope online shop Consumers, Consumer Experience positively mediates Advertising on the Electronic Word of Mouth of Shopee online store consumers, and Consumer Experience positively mediates Service Quality on the Electronic Word of Mouth of Shopee online store consumers